Utilization of Recycled PP-Talc Waste into Composite Products with the Hot Melt Mixing Method - Muhammad Ariya Afif; Muhammad Nicko Azharry Setyabudi; Mochamad Chalid; Bambang Priyono (Piston: Journal of Technical Engineering, 2022)
Polypropylene (PP) is one type of plastic material often used. As the materials' specifications get higher, PP is combined with other materials to achieve the desired characteristics. One of them is Talc. Behind its significant growth, there is one main problem, namely the mismanagement of plastic waste that causes environmental pollution. Therefore, one method that can overcome this problem is the recycling method. This research was conducted to investigate the characterization between pure and recycled materials and the optimum composition obtained to get finished goods that were close to materials using pure materials. This research was conducted using PP-Talc scrap with 20% and 30% talc content, then combined with dry and hot melt mixing methods. The alloy material was then tested using a Scanning Electronic Microscope (SEM), Universal Testing Machine (UTM), and Simultaneous Thermal Analyzer (STA). The results showed that the recycled material's morphological changes, mechanical properties, and thermal properties almost resembled the pure material. Specific ratios of 20% and 30% recycled PP-Talc gave rise to new morphological changes and mechanical properties.